Pemberian Hak Remisi Bagi Narapidana Narkotika Berstatus Justice Collaborator - Jupri Jupri (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
Indonesia as a paradise for narcotics distribution in Southeast Asia is inseparable from the influence of the Golden Triangle Syndicate, which is a narcotics distribution syndicate in accordance with the golden triangle line that covers three countries, Thailand, Laos and Myanmar. All in various narcotics cases revealed by the National Narcotics Agency or the Police as if the state was made helpless, some convicts who can be behind bars with Correctional Institutions (Lapas) are able to connect narcotics distribution in Indonesia. Therefore, it is necessary to uncover strategies through the role of Justice Collaborator but they are not easy to implement. This study discusses how to request remission rights for narcotics prisoners with Juctice Collaborator status in Lapas Class III Pohuwato. The research method used in this study is the normative-empirical legal research method. The results of the study show that remission is a right for inmates so that it cannot be eliminated, but it can be limited by the additional requirements that must be fulfilled, namely becoming a Justice Collaborator. From 28 narcotics prisoners, only 8 people get remission. As for prisoners who have not received remission, they are constrained in a letter of justice collaborator from investigators / prosecutors.